Stage-Specific Parasitism by a Mutualistic Partner Can Increase the Host Abundance - Nakazawa, Takefumi; Katayama, Noboru (Frontiers in Ecology and Evolution, 2020)
Mutualism is one of the major interaction types occurring in ecological communities, and has significant consequences for population dynamics and community structure. A major feature of mutualism is its context dependence; i.e., potentially mutualistic relationships may become parasitic or neutral depending on the abiotic conditions and presence of other species. Recently, stage structure has been recognized as an additional important factor underlying the context-dependence of mutualism, giving rise to the concept of stage-structured mutualism, which states that mutualistic partners at one life-history stage may become parasitic at other life-history stages. However, the ecological consequences of such a stage-structured interaction remain unknown. Here, we present a simplified one host–one partner model with a juvenile–adult stage structure of the host species, in which the partner species improves fecundity of the adult host but suppresses growth and maturation of the juvenile host. Numerical simulations identified two ecological conditions for stage-specific parasitism to counterintuitively increase host abundance: (i) the benefits derived by the adult host from the partner species are large and the costs imposed on the juvenile host by the partner species are small (the partner investment hypothesis), and (ii) host population growth is limited by adult reproduction instead of juvenile maturation (the ontogenetic asymmetry hypothesis). Although the partner investment hypothesis appears more intuitive, exhaustive parameter exploration revealed that the ontogenetic asymmetric hypothesis would be more likely to operate. This counterintuitive result implies that the dynamics of mutualistic interactions are more complex than previously thought. The present study provides novel insights into the ecological consequences of mutualism and illustrates the importance of the ontogenetic perspective of mutualism in community ecology. Further research is required in both empirical and theoretical approaches to better understand the mechanisms by which stage-structured mutualism mediates population dynamics and community structure in more complex systems.